Increasing Student Creativity in Supporting Physics Learning Outcomes with a Project-Based Learning Model - Rizaldi, Dedi Riyan Rizaldi (Balai Diklat Keagamaan Denpasar, 2024)
Research has been carried out with the aim of increasing student creativity in supporting physics learning outcomes. This research uses a project-based learning model. The type of research carried out was classroom action research with three stages, namely pre-cycle, cycle 1, and cycle 2. The research was conducted at MA Plus Nurul Islam Sekarbela on 20 Grade 12 students majoring in Mathematics and Natural Sciences. The data obtained in this research consists of quantitative and qualitative data. Quantitative data was obtained through tests by giving questions to obtain data on student creativity, while qualitative data was obtained through non-test data collection techniques that were produced through the process of observation and documentation regarding activities during the learning process. Based on data analysis and discussion, it was found that the average creativity rate increased from 65 to 75 and the percentage of student completion in physics learning increased from 40 to 70%. Apart from that, every indicator of student creativity appears to have increased periodically with each given cycle